The Role of Family in Meeting "Belongingness" and its Relationship with Psychological Security in a Sample of Adolescents in Hama City (Journal of Hama University, 2020)
The study aims at recognizing The Role of Family in meeting the " belongingness" and recognizing its Relationship with Psychological Security in a Sample of Adolescents, and finding out the differences between belongingness and Psychological Security according to gender.The sample of study includes (200) students at tha 10th class in public schools in Hama city,( 100) mala, (100) female.The researcher used the scales of  belongingness and Psychological Security.The results:1.There is a great role for the family in meeting the  Belongingness need for adolescents.2.Tere is a positive relational between  belongingness need and Psychological Security.3.There are statistical significant differences between the average performance of students on the scales of belongingness and Psychological Security according to gender on behalf of female.